2020
DOI: 10.3390/antiox9100948
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Activity and Concentration of Superoxide Dismutase Isoenzymes (Cu/Zn SOD, MnSOD) in the Blood of Healthy Subjects and Patients with Acute Pancreatitis

Abstract: This study was aimed at evaluating the changes in the concentration and activity of all superoxide dismutase isoenzymes (SOD1, SOD2, SOD3) in the blood of patients with acute pancreatitis (AP) and healthy subjects, taking into account the extracellular (plasma) and intracellular (erythrocyte lysate) compartment. The relationships between the activity/concentration of SODs, metal concentration and the markers of inflammation were evaluated. To assess the pro/antioxidative imbalance, the malonyldialdehyde (MDA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Additionally, our results showed increased total activity of SODs in erythrocytes of AP patients compared to healthy subjects, which could be related to increased MT concentration. MT, as a donor of Zn2+ ions, can take part in antioxidative defense and can regulate the activity of superoxide dismutase, especially its SOD1 and SOD3 isoenzymes [ 41 ]. The activity of Cu/Zn SOD strictly depends on metals such as Zn and Cu, where MT participates in its metabolism [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our results showed increased total activity of SODs in erythrocytes of AP patients compared to healthy subjects, which could be related to increased MT concentration. MT, as a donor of Zn2+ ions, can take part in antioxidative defense and can regulate the activity of superoxide dismutase, especially its SOD1 and SOD3 isoenzymes [ 41 ]. The activity of Cu/Zn SOD strictly depends on metals such as Zn and Cu, where MT participates in its metabolism [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patients were classified into the AP group on the basis of personal interviews, epigastric pain with touch sensitivity and medical and laboratory blood tests. Specific criteria for the inclusion of the patients in the study were described in [ 41 ]. The severity of the disease was determined according to the Atlanta classification.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanistic link between manganese and HbA1c and FPG is not fully understood; however, there is a possible role of the involvement of superoxide dismutase (SOD) enzymes [45,52,53]. There are three forms of SOD in mammals and manganese is a crucial component of manganese SOD (MnSOD) (it is worth noting that two of the other studied minerals-copper and zinc-are structural components of copper/zinc and extracellular SOD) [54]. SODs contribute to metabolic processes and protect cells against oxidative damage [45,52].…”
Section: Manganese Intake and Glucose Metabolismmentioning
confidence: 99%
“…This leads to elevated oxidant levels and, consequently, MnSOD may be upregulated to manage oxidative damage [60]. Ściskalska et al observed that patients with AP had a 3-fold increased MnSOD in erythrocytes compared with healthy controls and decreased plasma MnSOD, suggesting migration of MnSOD from other cells circulating in plasma (e.g., leukocytes and platelets) in the state of oxidative stress induced by AP [54]. Gut hormones (e.g., gastric inhibitory peptide and peptide YY) appear to increase circulating levels of pro-inflammatory cytokines, leading to persistent subclinical inflammation following an attack of AP [58,59].…”
Section: Manganese Intake and Glucose Metabolismmentioning
confidence: 99%
“…Sciskalska et al [14] assessed the impact of acute pancreatitis (AP) on changes in the concentrations and activities of all three superoxide dismutase (SOD) isoenzymes and the interrelationships between the different isoenzymes and the oxidative and inflammatory status. Finally, the effect of single-nucleotide polymorphism (SNP) in the SOD1 gene (rs2070424) was also taken into consideration.…”
mentioning
confidence: 99%